Sprint performance under heat stress: A review - Girard, O.; Brocherie, F.; Bishop, D. J. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Training and competition in major track-and-field events, and for many team or racquet sports, often require the completion of maximal sprints in hot (>30 °C) ambient conditions. Enhanced short-term (<30 s) power output or single-sprint performance, resulting from transient heat exposure (muscle temperature rise), can be attributed to improved muscle contractility. Under heat stress, elevations in skin/core temperatures are associated with increased cardiovascular and metabolic loads in addition to decreasing voluntary muscle activation; there is also compelling evidence to suggest that large performance decrements occur when repeated-sprint exercise (consisting of brief recovery periods between sprints, usually <60 s) is performed in hot compared with cool conditions. Conversely, poorer intermittent-sprint performance (recovery periods long enough to allow near complete recovery, usually 60-300 s) in hotter conditions is solely observed when exercise induces marked hyperthermia (core temperature >39 °C). Here we also discuss strategies (heat acclimatization, precooling, hydration strategies) employed by "sprint" athletes to mitigate the negative influence of higher environmental temperatures.